Analyzing the Impact of Social Media Marketing, Green Marketing, and Developer Reputation on Property Purchase Intention - Dirgayasa, I Made; Darma, Gede Sri (Journal of Ecohumanism, 2024)
This research explores property purchase decisions regarding Consumer Trust, influenced by Social Media Marketing, Developer's Reputation, and Green Marketing. This research was conducted on 200 property customers in Indonesia and carried out online. The research results show that Social Media Marketing, Developer's Reputation, Green Marketing and Consumer Trust directly influence Purchase Intention. Social media marketing influence consumer trust, but green marketing and developers' reputations do not influence consumer trust. Furthermore, Consumer Trust is proven to mediate Social Media Marketing and Property Purchase Intention. The Central Statistics Agency shows an imbalance in the backlog (number of needs for home ownership) throughout 2023. There is a significant decrease from 16.14 million units (2022) to 14.84 million units in 2023. The results of this research can be used as material for practitioners to increase purchasing decisions for property businesses that are more profitable in the long term.